Practicing and memorizing the pieces for classical guitar students / Mohamad Fakhruddin Abd Razak - Abd Razak, Mohamad Fakhruddin (2020)
Practicing and memorizing was an important things for music students, it helps students develop and improve their self on playing or perform. This research focuses on classical guitar students of Faculty of Music in UiTM Shah Alam. This research will be looking on three main objectives, which to describe how classical guitar students practice their pieces effectively and to identify how classical guitar students practice for the memorization pieces This study will be useful for classical guitar students who interested to know the benefits and advantages that they will gain when they are practicing and memorizing effectively. The findings of this study can be the guideline for classical guitar students to know how the advantage when they practice their pieces effectively. It also give an advantage to students when they perform. The findings will also elaborate classical guitar students practice for the memorization pieces.